Advances in the Management of Pemphigus Vulgaris: A Review Article (Global Journal of Medical Research, 2022)
Pemphigus vulgaris PV is a debilitating autoimmune disease that seems to have genetic predilection In most cases it appears to affect mainly oral mucosa but can also occur in conjunction with skin lesions affecting different areas of the body Oral involvement is characterized by the presence of erosions whereas skin lesions are mainly flaccid bulla early or erosions late PV is characterized by the formation of extremely fragile bulla that frequently rupture forming denuded painful easily bleeding erosions that often become crusted
Keywords: flaccid bulla; desmosomes; nikolsky sign; asboe-hansen sign; immunofluorescence